EKSISTENSI NORMA AGAMA DAN PANCASILA DALAM PEMBENTUKAN PERATURAN PERUNDANG-UNDANGAN - Sirajuddin M (Nuansa : Jurnal Studi Islam dan Kemasyarakatan, 2015)
Indonesian is constitutionally as the state of Pancasila and not as a religious state, but the state is able to accommodate a number of religious norms in the formation of legislation. This typical problem is the primary focus of this study of how is the existing of intensified relations between the values/norms of religious life in the community and Pancasilaas well as how is the existence of religious norms as one of the existential reality of living among the people and the society which later became the part of the values which raised and contained in Pancasila. The results of this study is the birth of the legislation and local regulations with religion nuanced in the constitutional factual reality, so the ideology of Pancasila and the Constitution-NRI 1945 can absorb and accommodate the diversity of religious, cultural, political, economic and others.Although the State of Indonesia is not the state of religion, but Pancasila as an ideology